1988
DOI: 10.1002/bjs.1800750318
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of abdominal aortic aneurysm in men with peripheral vascular disease: Screening by ultrasonography

Abstract: A study was carried out to see if an ultrasonic examination of the abdominal aorta was indicated in every patient who attended an outpatient clinic with peripheral vascular disease (PVD). One hundred consecutive patients were studied and compared with a control group. The incidence of abdominal aortic aneurysm (AAA) in the control group was 2 per cent. In the study group, the male patients had an incidence of 20 per cent of aneurysm and ectasia, while the female patients had an incidence of 12 per cent. Of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(33 citation statements)
references
References 11 publications
1
31
0
1
Order By: Relevance
“…1 Data from large cross-sectional studies are consistent with the prospective data, supporting associations of AAA with male gender, age, cigarette smoking, serum cholesterol, and coexisting cardiovascular diseases. 3,11,31 A study of over 75 000 veterans ages 50 to 79 years identified 1031 AAA by ultrasound and reported associations with stature, serum cholesterol, and hypertension. A family history of aneurysm, reported by 5% of these veterans, was associated with a nearly 2-fold greater odds ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Data from large cross-sectional studies are consistent with the prospective data, supporting associations of AAA with male gender, age, cigarette smoking, serum cholesterol, and coexisting cardiovascular diseases. 3,11,31 A study of over 75 000 veterans ages 50 to 79 years identified 1031 AAA by ultrasound and reported associations with stature, serum cholesterol, and hypertension. A family history of aneurysm, reported by 5% of these veterans, was associated with a nearly 2-fold greater odds ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, including the CHS, have reported a higher likelihood of other CVD among aneurysm patients. 1,6,8,31 Studies of children and young adults found associations of aortic (as well as coronary) plaque with lipid and glucose abnormalities, hypertension, and smoking. [33][34][35][36] It is not known whether such aortic lesions observed in youth are precursors of adult aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…In a group of male patients with peripheral arteriopathy, Allardice et a1. 29 reported that the incidence of AAA was 17%.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal aortic aneurysm is associated with atherosclerosis, with prevalence rates of 10% to 16% in patients known to have femoral occlusive disease. 13 It is also strongly associated with coronary artery disease; a recent study found that 36% of patients with known aortic aneurysm had severe coronary artery disease on angiography.…”
Section: Discussionmentioning
confidence: 99%